Making Science: New Generations of Collaborative Knowledge Production. (May 2015) - Binz-Scharf, Maria C.; Kalish, Yuval; Paik, Leslie
Research scientists have become increasingly dependent on collaborations across laboratories and organizations to maintain their productivity. However, the increased specialization of individual laboratories works against the current drive toward understanding systems in the sciences. Consequently, there is a tension between the rising importance of collaborative efforts and the practical and structural challenges in establishing and managing such collaborations. Combining ethnographic case studies of three biology research labs with network data of their larger scientific community, we explore the changing process of scientific knowledge production in the age of Big Science. We find that virtual technologies open up the knowledge process as scientists have easier access to data, publications, and each other. At the same time, we find that these technologies—specifically scientific databases—do not eradicate the social aspects of scientific knowledge production as collaborative structures in science remain relatively unchanged. We discuss the implications for theory and practice of this seemingly contradictory character of scientific knowledge production.